802 PERIOPERATIVE AND SHORT-TERM OUTCOMES FOR PRIMARY ANTIREFLUX SURGERY: FUNDOPLICATION VS. RNY RECONSTRUCTION. (17th September 2021) - Razia, Deepika; Razia, Deepika; Mittal, Sumeet K
Abstract: : Laparoscopic fundoplication is the gold standard for treatment of gastroesophageal reflux disease (GERD); however, RNY reconstruction may be an alternative option in patients with complex pathophysiology and other risk factors. This study aimed to compare perioperative and short-term outcomes between primary fundoplication and RNY reconstruction. Methods: After IRB approval, a prospectively maintained esophageal surgery database was retrospectively reviewed to identify patients who underwent primary fundoplication or RNY reconstruction from September 2016 to July 2020. We retrieved perioperative outcomes (operative time, length of hospital stay, intraoperative and postoperative complications) along with GERD-Health-Related Quality of Life (HRQL) scores at annual follow-up. Results: During the study period, 226 patients underwent surgery (fundoplication: 210; RNY: 16). The most common indication for RNY was severe esophageal dysmotility or morbid obesity. There was only one conversion to open surgery due to adhesions (fundoplication group). The operative time, length of hospital stay, and ICU stay were significantly lower in the fundoplication group. Rates of intraoperative (fundoplication: 3% vs RNY: 0) and postoperative complications (Clavien-Dindo ≥II) (fundoplication: 3% vs RNY: 6%) were not significantly different between groups. Both groups had a significant and similar improvement of GERD-HRQL scores 1 year after surgery (Table 1). Conclusion: Primary antireflux surgery is associated with low perioperative morbidity and excellent short-term outcomes. RNY reconstruction and fundoplication have similar outcomes. More liberal use of RNY reconstruction as the primary antireflux surgery in patients at high risk of failure with fundoplication should be explored.